THE USE OF THE NUMBERED HEAD TOGETHER LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES ON THE SUBJECT OF ADDING AND SUBTRACTING INTEGERS IN GRADE IV SD - I Kadek Eka Saputra Wijaya; I Ketut Kertayasa; Ni Putu Satya Narayanti (JATMIKA : Journal Education and Learning of Elementary School, 2023)
This study aims to improve student learning outcomes throught the use of the Numbered Head Togther (NHT) learning model in grade IV SD. Classroom Action Research (CAR) was used as design research that consist of plan, implementation, observation, and reflection. Data analysis in this study consisted of two ways, namely quantitative data analysis and qualitative data analysis. By using NHT learning model, the student achievement were increased. This is as seen in the results of the post-test cycle I and Cycle II. At the first cycle percentage of classical obserption was 66,14% and classical learning completeness was 50%. While at the second cycle percentage of clasiccal obserption was 81,28% and clasiccal learning completeness was 85,71%. So it can be concluded that the use of the NHT learning model can improve student learning outcomes.